Histone Variants and Composition in the Developing Brain: Should MeCP2 Care? - Zago, Valentina; Pinar-CabezaDeVaca, Cristina; B. Vincent, John; Ausio, Juan (Current Topics in Medicinal Chemistry, 2017)
Specific compositional chromatin features distinguish brain/neuronal chromatin from that of other tissues and are critical to this organ and cell type development and neuroplasticity. These features include a significant turnover of the major constitutive chromosomal proteins, including the (canonical) replication-dependent histones, the replication-independent replacement histone variants, as well as the chromatin associated transcriptional regulator MeCP2 (methyl CpG binding protein 2). Alterations of histones and MeCP2 have already been implicated in many brain disorders. Despite the relevance of histone variants to chromatin structure and function, only recently has some exciting literature started to re-emerge that directly relates them to neuron plasticity and cognition. However, the amount of information available on the functional role of these histones is still very limited. The purpose of this review is to focus attention to this important group of chromatin proteins, which, in the brain, possess overlapping structural and functional roles with the highly abundant presence of MeCP2. There is an imperative need to understand how all these proteins communicate with each other, and future research will hopefully provide us with answers.
Keywords: Histone variants